2016
DOI: 10.1007/s00592-016-0950-1
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes education of patients and their entourage: out-of-hospital national study (EDUCATED 2)

Abstract: In France, diabetic patients and their entourage are inadequately educated. Their education benefits most from care by a diabetologist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In contrast, a study conducted in France on people with diabetes showed that the main contributing factor to the education of patients about diabetes was follow-up and counseling by a diabetologist compared to nurse-only counseling. 16 However, the later study examined general community nurses who only assisted patients with insulin injection and glucose monitoring and not a nurse specialist or an RN with specific training in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a study conducted in France on people with diabetes showed that the main contributing factor to the education of patients about diabetes was follow-up and counseling by a diabetologist compared to nurse-only counseling. 16 However, the later study examined general community nurses who only assisted patients with insulin injection and glucose monitoring and not a nurse specialist or an RN with specific training in diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…24 The Standards for Quality Improvement Reporting Excellence checklist was used for preparing this article. 18 Minitab software V.17 was used for data analysis.…”
Section: Contextmentioning
confidence: 99%
“…Health education provided by prehospital medical staff to patients with diabetes needed to be enhanced. 18 Diabetes education is essential for self-management and positive health-related outcomes. 19 Therefore, training HMCAS paramedics to provide appropriate diabetes education could reduce the patients’ 999 callback rates, thereby reducing the demand on HMCAS resources.…”
Section: Introductionmentioning
confidence: 99%
“…10–12 Some self-care skills may be difficult to acquire during TPE, including managing uncontrolled and severe hypoglycaemia. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Most TPE programmes only offer instruction but neglect skills necessary for everyday life 10–12. Some self-care skills may be difficult to acquire during TPE, including managing uncontrolled and severe hypoglycaemia 13…”
Section: Introductionmentioning
confidence: 99%